Diagnosing Pilgrimage Common Diseases by Interactive Multimedia Courseware (Baghdad Science Journal, 2022)
In this study, we attempt to provide healthcare service to the pilgrims. This study describes how a multimedia courseware can be used in making the pilgrims aware of the common diseases that are present in Saudi Arabia during the pilgrimage. The multimedia courseware will also be used in providing some information about the symptoms of these diseases, and how each of them can be treated. The multimedia courseware contains a virtual representation of a hospital, some videos of actual cases of patients, and authentic learning activities intended to enhance health competencies during the pilgrimage. An examination of the courseware was conducted so as to study the manner in which the elements of the courseware are applied in real-time learning. More so, in this research, a discussion on the most dangerous diseases which may occur during the season of pilgrimage is provided. The use of the multimedia course is able to effectively and efficiently provide information to the pilgrims about these diseases. This technology performs this task by using the knowledge that has been accumulated from past experience, particularly in the field of disease diagnosis, medicine and treatment. The courseware has been created using an authoring tool known as ToolBook instructor to provide pilgrims with quality service.